(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Internal customers (employees) are like the ladder of success, brand ambassadors, or the face of any company who needs to satisfy and gratify to hit the coveted growth. For organizations, it is very crucial to know how employees feel while working and how employees perceive their work. Employee engagement helps employers to understand the expectations of employees and sketch a path for employers to deliver the expectations of employees and a course for employees where they can feel both connected (realization of goals) and motivated (willingness to achieve the goals). This paper focuses on employee engagement, a factor for managing talent, in an attempt to identify how engagement of employees is correlated (positively or negatively) with managing talent and how researchers perceive employee engagement.